Implicit and explicit racial prejudice and stereotyping toward Black (vs. White) Americans: The prevalence and variation among genetic counselors in North America. Issue 2 (7th November 2022) - Hagiwara, Nao; Duffy, Conor; Quillin, John
Abstract: Research has shown that patient experiences and outcomes of genetic counseling are not equitable across racial categories, disadvantaging Black patients relative to White patients. One major factor contributing to such racial disparities might be genetic counselor racial bias. The present study examined the prevalence of and variation in racial bias toward Black (vs. White) Americans among genetic counselors in North America. This study extends the current literature of racial disparities in experiences and outcomes of genetic counseling by distinguishing prejudice (negative feelings or attitudes) and stereotyping (beliefs) at the implicit and explicit levels as well as by including both certified genetic counselors and genetic counseling trainees. Two‐hundred and fifteen genetic counselors (107 genetic counselors Board‐certified by the American Board of Genetic Counseling, 108 genetic counseling trainees from Accreditation Council for Genetic Counseling accredited programs) completed four measures in a random order: the Race Implicit Association Test (IAT, for implicit prejudice), feeling thermometer (for explicit prejudice), the Medical Cooperativeness IAT (for implicit stereotyping), and a self‐report measure of explicit stereotypes (for explicit stereotyping). On average, genetic counselors (both certified genetic counselors and genetic counseling trainees) were slightly to moderately in favor of White Americans over Black Americans at the implicit level. They were also slightly more likely to associate "medically cooperative" stereotypes with White Americans more than Black Americans implicitly. In contrast, genetic counselors, on average, did not display either explicit prejudice or explicit negative stereotyping, which may reflect social desirability concerns among genetic counselors. However, genetic counselors as a group strongly endorsed stereotypes related to mistrust (mistrustful of the healthcare system, skeptical of genetic testing, mistrustful of genetic counselors) to be more true for Black (vs. White) Americans. Finally, our study revealed relatively large variability in each type of bias across genetic counselors. Future research should examine how such variability in each type of bias is associated with patient experiences and outcomes of genetic counseling.